The Effects of Situational and Personal Characteristics on Consumer Complaint Behavior in Restaurant Services - Kim, Jong; Chen, J. (Routledge, 2010)
This study developed and tested a model to investigate the effects of situational and individual differences on consumers' propensity to complain in a restaurant setting. A structural equation modeling analysis revealed that convenience of complaining and expectation of resultant benefits, consumers' attitude toward complaining, consumer involvement with a dining experience (e.g., dining on a special occasion and expensive food), and perceived self-importance, are factors associated with the likelihood of engaging in complaining behavior. Theoretical and managerial implications of the results of the study are discussed in detail.